Systematic review and meta-analysis of propranolol in the prevention and treatment of post-traumatic stress disorder - Li, Haipeng; Zhang, Zhengrong; Yang, Shaojie; Zhu, Guoqi (Frontiers in Pharmacology, 2025)
ObjectiveThis systematic review and meta-analysis aim to comprehensively evaluate the efficacy of propranolol in the prevention and treatment of post-traumatic stress disorder (PTSD), with a focus on its improvement of core PTSD symptoms.MethodsA literature search was conducted across multiple databases (including PubMed, Cochrane, Web of Science, and Embase), with the search cutoff date in October 2024. The studies included randomized controlled trials (RCTs) investigating pharmacological treatments for PTSD. PTSD symptoms were assessed using standardized clinical scales, including the Clinician-Administered PTSD Scale (CAPS) and the PTSD Checklist (PCL). The primary outcome was the improvement in PTSD symptoms.ResultsSeven studies met the inclusion criteria for the meta-analysis. The studies showed low heterogeneity, with a chi-squared value of 2.56 (df = 6, p = 0.86) and I2 = 0%. The overall effect test indicated significant improvement in PTSD symptoms after propranolol intervention (Z = 2.32, p = 0.02). These findings suggest that propranolol has a statistically significant effect on reducing the severity of PTSD symptoms, with a moderate effect size according to Cohen’s criteria.ConclusionThis systematic review and meta-analysis provide preliminary evidence supporting the possible role of propranolol in alleviating PTSD symptoms. Future researches are needed to further clarify the therapeutic potential, mechanisms of action, and long-term safety of propranolol in PTSD treatment.